GARCH Model For Forecasting Stock Return Volatility In The Infrastructure , Utilities And Transportation Sectors - Faizul Mubarok; Eni Sutrieni (STIE PGRI Dewantara Jombang, 2020)
The stock market is continuously changing with uncertainties that can create risks. Prompt information dissemination and rapid capital flow will cause stock price fluctuations, causing volatility in stock prices. This research examines the behavior of volatility patterns in the infrastructure, utility, and transportation sectors using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model. This study uses monthly data from January 2014 to December 2019. The results show that the volatility of all stocks in the study is influenced by the previous month's error and volatility return. Investors and securities analysis can use these results in making decisions to invest in the infrastructure, utilities, and transportation sectors.